2023
DOI: 10.1371/journal.pgph.0001631
|View full text |Cite
|
Sign up to set email alerts
|

Can cash transfer interventions increase contraceptive use and reduce adolescent birth and pregnancy in low and middle income countries? A systematic review and meta-analysis

Dylan Kneale,
Abel Kjaersgaard,
Malica de Melo
et al.

Abstract: Becoming pregnant and giving birth under the age of 20 is associated with a range of adverse social, socioeconomic and health outcomes for adolescent girls and their children in Low and middle income countries. Cash transfers are an example of a structural intervention that can change the local social and economic environment, and have been linked with positive health and social outcomes across several domains. As part of a wider review of structural adolescent contraception interventions, we conducted a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In sub-Saharan Africa unlike in other regions, cash transfer programs tend to focus more on addressing household's immediate needs such as food security and survival, although programs that target behavioral change to reduce prevalence of sexual transmitted infections and early marriage and childbearing are also common ( 35 ). In summary, evidence from the systematic review and meta-analysis studies has shown that cash transfer programs can reduce adolescent pregnancy and childbearing ( 36 ), poverty, and vulnerabilities ( 37 ), as well as improve mental health ( 38 ) in Low- and Middle-Income Countries (LMICs).…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa unlike in other regions, cash transfer programs tend to focus more on addressing household's immediate needs such as food security and survival, although programs that target behavioral change to reduce prevalence of sexual transmitted infections and early marriage and childbearing are also common ( 35 ). In summary, evidence from the systematic review and meta-analysis studies has shown that cash transfer programs can reduce adolescent pregnancy and childbearing ( 36 ), poverty, and vulnerabilities ( 37 ), as well as improve mental health ( 38 ) in Low- and Middle-Income Countries (LMICs).…”
Section: Introductionmentioning
confidence: 99%